Key policy questions for ex-ante impact assessment of European agricultural and rural policies. (8th September 2021) - Coderoni, Silvia; Helming, John; Pérez-Soba, Marta; Sckokai, Paolo; Varacca, Alessandro
Abstract: Policies in the agricultural and rural sectors are of key importance in shaping their sustainable development. These policies are changing from market-based policies to policies that aim to influence farmers' decision-making. Thus, the scientific literature supporting evidence-based policy-making must develop models that simulate individual decision-making (IDM) by farmers. This study aims to understand key policy objectives, related policy questions and benchmark scenarios relevant to the European agricultural sector to define the research agenda for a suite of IDM models. This research goal has been addressed following a five-step process that involved different research tools and heterogeneous actors, including key stakeholders. Results suggest that environmental policy objectives are the most relevant for European agriculture in the coming decades. Thus, the scenario modelling exercise should focus mainly on the agri-environmental policies' impacts while properly considering the potential trade-offs between economic and environmental objectives.